Peningkatan teknologi bagi agroindustri pliek-u sebagai upaya pelestarian kearifan lokal di Aceh [Technology improvement on pliek-u agroindustry as an effort to maintain a local wisdom in Aceh] - Khathir, Rita; Rahmawati, Marai; Yunita, Yunita (Buletin Pengabdian, 2024)
Pliek-u is a specialty food product in Aceh with local wisdom values that should be preserved. The Program of Community Service Based Product (PKMBP) aimed to improve the pliek-u agro-industry by adapting simple processing technologies so that it could lighten work, produce quality products, and attract the interest of the younger generation as pliek-u entrepreneurs in future. The method applied consist of surveys, preparation of tools and materials, assembly of a solar tunnel dryer type Hohenheim Aceh and a hydraulic press, training and dissemination of technology through field schools, and evaluation of the program with pre-tests and post-tests. Data analysis was carried out using the Wilcoxon rank test with alpha of 5%. The results of the program were the construction of 1 unit of Hohenheim Aceh tunnel dryer, 1 unit of hydraulic press, and the implementation of training and dissemination activities which have been published in the form of videos on YouTube media and press releases through online media. The results of the Wilcoxon rank test also showed that of the 13 participants whose data were valid, 100% of participants received positive rankings and the pre-test scores were significantly different from the post-test scores. Thus, it can be concluded that the program carried out has contributed to increasing the knowledge, expertise capacity, and interest of participants in pliek-u processing technologies since the profile of conventional agroindustry can be transformed to be better agroindustry by the use of solar tunnel dryer type Hohenheim Aceh and hydraulic press. In addition, the use of technologies will ensure the halal requirement of pliek-u.